Personal Recommender for Gold Investment Portfolios - Yusop, Nor Iadah; Yi, Eng Qian (Multidisciplinary Applied Research and Innovation, 2023)
Customers frequently buy digital gold from companies that offer higher profits. In line with this, a company by the name of ABC offers units of gold-based Gold Enhancement (GE) for a fixed unit price in US dollars. With GEs, the consumer can benefit at a rate that is five or ten times greater than the spread between the purchase and sell prices, respectively. It is interesting to note that the customer can sell if the desired level of net profit is achieved. However, the existing ABC system does not offer such data. In order to determine the ideal time to release a particular unit, the user must manually compute to see if the target percentage of profit is met. As a result, the consumer may miss the ideal opportunity to sell his unit and, more crucially, he may do so at a loss. Thus, automating the computation is essential for the user to obtain prompt advice for selling a unit in his portfolio. This is what the developed application, Personal Recommender for Gold Investment Portfolio (PRGI), aims to do. The Agile Method, a software development methodology, was used to develop PRGI. Android Studio serves as the main integrated development environment (IDE) tool, and it was created using Visual Studio Code and the Cpanel database. PRGI has successfully been developed to satisfy the needs of the user. For a more satisfying experience, the application can be further enhanced by incorporating an automated approach for less data entry work. Additionally, delivering the notification as a pop-up notification or something similar can be more effective than sending it by email.